2019
DOI: 10.1111/brv.12508
|View full text |Cite
|
Sign up to set email alerts
|

Lianas as a food resource for herbivorous insects: a comparison with trees

Abstract: Woody climbers or, 'lianas', are one of the features that characterise rainforests. They contribute substantially to plant diversity and leaf biomass which makes them a potentially important food source for herbivores. Here, we focus on insect herbivores, folivores in particular, to show how disparities in the quantitative and qualitative availability of leaves between lianas and trees may differentially influence insect folivory and the herbivore communities themselves. We develop a conceptual model and show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 164 publications
(202 reference statements)
0
22
0
2
Order By: Relevance
“…important for maintaining biodiversity (Schnitzer and Carson, 2001). Accordingly, lianas may enhance recovery from disturbance, including soil (Tang et al, 2012), seed diversity (César et al, 2017) and fauna (Ødegaard, 2000;Arroyo-Rodríguez et al, 2015), and may provide protection from fire (Uhl et al, 1988), lightning (Yanoviak, 2013), wind (Putz, 1984b), cyclones (Unwin et al, 1986), weeds (Goosem and Tucker, 2013) and herbivory (Odell et al, 2019). We collectively refer to these protective influences of lianas as their "bandage effect".…”
Section: (B) Benefits To Forestsmentioning
confidence: 99%
“…important for maintaining biodiversity (Schnitzer and Carson, 2001). Accordingly, lianas may enhance recovery from disturbance, including soil (Tang et al, 2012), seed diversity (César et al, 2017) and fauna (Ødegaard, 2000;Arroyo-Rodríguez et al, 2015), and may provide protection from fire (Uhl et al, 1988), lightning (Yanoviak, 2013), wind (Putz, 1984b), cyclones (Unwin et al, 1986), weeds (Goosem and Tucker, 2013) and herbivory (Odell et al, 2019). We collectively refer to these protective influences of lianas as their "bandage effect".…”
Section: (B) Benefits To Forestsmentioning
confidence: 99%
“…Lianas may generally benefit insectivorous birds by increasing the abundance of arthropods (Ødegaard 2000, Yanoviak and Schnitzer 2013, Adams et al 2019, Odell et al 2019. Lianas add a complex array of stems to the forest understory, which provide food sources for herbivorous insects (i.e., liana leaves and stems).…”
Section: Discussionmentioning
confidence: 99%
“…Liana fruits, flowers, leaves, and stems are also valuable food resources to the animal community. Thus, lianas increase heterogeneity throughout the vertical profile of tropical forests, which can provide myriad habitat and food resources that maintain animal abundance and diversity (Yanoviak and Schnitzer 2013, Arroyo‐Rodriguez et al 2015, Lambert and Halsey 2015, Adams et al 2017, Odell et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Lianas are one of the key growth forms in tropical and subtropical forests (Schnitzer & Bongers, 2002), which are important for providing canopy connectivity, food sources, and habitats for animals (Schnitzer & Bongers, 2002; Odell et al. , 2019). Previous studies have shown that lianas employ acquisitive strategies, i.e.…”
Section: Introductionmentioning
confidence: 99%